2017
DOI: 10.4108/eai.18-7-2017.152898
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Using Asynchronous Remote Communities (ARC) for Researching Distributed Populations

Abstract: Existing research methods are largely intended to be conducted co-located and synchronously with a study population, but this approach is not feasible with remote or distributed populations. We describe a needs assessment study we conducted on Facebook. We report on our use of adapted versions of commonly used HCI research methods and lessons learned from this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…Unlike MacLeod et al [4], we found that participants were less likely to complete free text activities that allowed them to remain on the platform. Instead, surveys had better overall completion rates (c.f.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Unlike MacLeod et al [4], we found that participants were less likely to complete free text activities that allowed them to remain on the platform. Instead, surveys had better overall completion rates (c.f.…”
Section: Discussioncontrasting
confidence: 96%
“…Activities can be private, such as completing a survey off Facebook, or public, such as discussing a post. MacLeod et al [4] piloted the ARC method with people with rare diseases to gain a deeper understanding of their challenges and needs. The method has also been used successfully for pregnant women and new mothers [6] and people living with HIV [5].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, co-located methods (where researchers and participants are physically present together) are not possible because of access, mobility, physical, social, political, and economic constraints. In addition, researchers may not be in a location with access to the target population -for example when a research team with limited resources needs to accommodate the perspective of people with rare diseases in a health system design, since only 10% of the world's population has a rare disease, the research team must utilize alternative methods to gain their perspective [12]. We found that sociotechnical researchers are overcoming these barriers to gain a deeper sense of people's needs by studying how people currently appropriate social media to discuss their health.…”
Section: Resultsmentioning
confidence: 99%
“…MacLeod et al developed the Asynchronous Remote Communities (ARC) method that builds on remote needs assessment methods, which has included instant messaging [29], email [30], phone [30], and video [31] interviewing methods. They qualitatively investigated the needs of people with rare diseases by engaging 11 participants in a 22-week study on a private Facebook group [12,16,17]. The researchers found that online communities provided invaluable support, but participants needed more tangible support.…”
Section: Appropriating Mainstream Technologymentioning
confidence: 99%
“…The sample size was determined based on previous studies of asynchronous remote community research, with studies ranging from 13 participants to 48 participants (21)(22)(23)(24)(25). As the secret Facebook group takes place over a longer period of time, a larger group of participants can be accommodated in comparison to an in-person focus group or an online synchronous focus group (25).…”
Section: Participants and Recruitmentmentioning
confidence: 99%